POLA IMPLEMENTASI ALOKASI ZISWAF DALAM PENYEDIAAN AKSES PENDIDIKAN BAGI KAUM DHUAFA - KHURUL AIMMATUL UMMAH; AHMAD RIYADI; SRI HERIANINGRUM (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2018)
The education sector is an escalator to the nation's future moral, progressive, prosperous, dignified and prosperous. But the reality in Indonesia at this time not all walks of life can benefit from a good education. There are very many people who can not enjoy a proper education due to economic factors, or inability to access it. Islam has used philanthropy in removing economic and social disparities within a community in which ZISWAF (Zakat, Infaq, Sedekah and Wakaf). When this has been a lot of institutions that focus on social fund through the instrument ZISWAF, but the distribution of these funds are still focused towards sectors of the economy, even to meet the needs of the consumer. Indeed the education sector is also one of the strategic sectors which should be considered as a form of manifestation in pencampaian future for poor people better.Through research that uses qualitative approach aims to be able to determine the pattern of distribution of funds ZISWAF implementation by collectors in the provision of access to education for the poor, so as to explain and provide information to the public in the disbursement of funds ZISWAF to providing access to education for the poor quality. By using kompratif study researchers compared patterns of implementation ZISWAF implemented by the two institutions that became the object of research is Smart Ekselensia, and Junior High School champion, then the results of the analysis will be processed using the method of Spradley. Based on the results of analysis show that the implementation of the distribution ZISWAF in procuring access to education for these three agencies do have differences, but it overlooks impact both in providing quality education for the poor.